2010
DOI: 10.1039/b901255a
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and biological applications of photo-labile organic molecules

Abstract: Photo-labile molecules have been widely used not only in organic synthesis but also in biological study. The chemistry of the typical photo-labile organic molecules, including their structure, mechanism underlying their photo-lability and strategies to integrate them with biomolecules, is reviewed to illustrate the structural basis for photo-activable caged compounds. Biological applications of representative photo-labile caged molecules were also illustrated for a general understanding on the important roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
196
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(198 citation statements)
references
References 49 publications
0
196
0
2
Order By: Relevance
“…1b). Normally, irradiation with 365 nm (ultraviolet) light is used to photocleave the bond and thus release the active form of a compound [13][14][15]. In this report, we demonstrated that the ester bond could be cleaved by 18 FDG.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…1b). Normally, irradiation with 365 nm (ultraviolet) light is used to photocleave the bond and thus release the active form of a compound [13][14][15]. In this report, we demonstrated that the ester bond could be cleaved by 18 FDG.…”
Section: Introductionmentioning
confidence: 64%
“…1a). Recognizing that many medicinal applications of caged drugs have been impeded by the poor penetrating ability of the light source [13][14][15][16], we feel that this method could provide a critical step forward for in vivo diagnostics and therapy. Since radioactive isotopes can be tuned and localized to tissues within the body, the proposed photoactivation reaction should have no depth limitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ein aktueller Über-sichtsartikel diskutiert die Strukturen, Mechanismen und Eigenschaften einiger geläufiger photolabiler Schutzgruppen, darunter Nitrobenzyl-, Cumarin-und Hydroxyphenacyl-Derivate. [23] Die Nitrophenylverbindungen können mit Nah-UV-Licht der Wellenlänge l = 350 nm photolysiert werden; dieser Wert liegt innerhalb des UVA-Bereichs (l = 315-400 nm). Anders als UVB (l = 280-315 nm) und UVC (l = 100-280 nm) wird UVA nicht von DNA absorbiert und verursacht daher keine direkten DNA-Schäden.…”
Section: Abgeschlossene Metallkäfigeunclassified
“…18) It was reported that so-called "caged" drugs, particularly those containing photocleavable protecting groups, play important roles in the control of bioactivities. [19][20][21][22][23][24][25][26] As general (not limited to metal chelators) examples of "caged" biologically active compounds, Hoffman's group reported the design and synthesis of "caged ATP," which is an ATP molecule that is protected by a photocleavable (2-nitro) phenylethyl group, to investigate the function of the Na : K pump in human red blood cells. 19) Hess' group also reported on the use of N-nitrobenzyl serotonin, a "caged serotonin," in a kinetic study of the serotonin 5-HT 3 receptor.…”
Section: -Hydroxyquinoline (Hq)-based Compounds Have Recently Been Pmentioning
confidence: 99%